Pengembangan Alat Praktikum Sederhana Sebagai Media Praktikum Mahasiswa - Widayanti, Widayanti; Yuberti, Yuberti (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2018)
This study aimed to (1) find out how to develop a simple experimental tool for Meldeâs experiment, (2) determine the feasibility level of simple meldeâs experiments. The method used in this research was Research and Development which was adapted from Thiagarajan (4D) including define, design, develop and dissemination. This research was done until the development stage. The results of the study includes the simple experimental practice of meldeâs experiment and the feasibility level of simple experimental tool of meldeâs experiment.  Based on 86,7% of expertsâ judgement, the simple experimental tool is categorized into very feasible. The result of trial experiment in one on one, small group and fields are 83.3%, 87.5% and 90.9 % respectively. The three experimental results were categorized into highly feasible. Thus, the development of simple experimental tools for meldeâs experiment is worthy as a learning media.